Greed For Money In Scott Smith's A Simple Plan (1993):An Individual Psychological Approach - Adyatama, Bagus Surya (2016)
The problem of this study is to reveal how major character reflects his greed for in his life. The objective of this study is to analyze the novel based on the structural elements and to analyze the novel based on the individual psychological approach. The type of this research is qualitative research. Type of data of the study is novel taken from two data sources: primary and secondary. The primary data source is the A Simple Plan novel published in 1993. While the secondary data sources are other materials taken from books, author's biography, essay, comments, critics and internet related to the study. Both data are collected by conducting library research and analyzed by descriptive analysis. Based on the analysis, the researcher portrays some conclusions. First, based on the structural analysis of each elements, it shows that the character and characterization, setting, plot, point of view, style, and theme. Second, based on the individual psychology analysis, the study shows that the problem faced by the major character is his own psychology condition to decide the appropriate ways for his life. Scott Smith tells that the problem of the major character causes the conflict of his social life because of his greed and cause some effect to inferiority feeling, striving to superiority, creative self, style of life, social interest, functional finalism of the main character. Keywords: A Simple Plan, greed for money, and Individual Psychological Approach.